How feasible is coastal management? A social benefit analysis of a coastal destination in SW Spain. (June 2017) - Alves, Bruna; Ballester, Ramon; Rigall-I-Torrent, Ricard; Ferreira, Óscar; Benavente, Javier
Abstract: Very few assessments of the beach recreational experience value have been made in Spain. This is both surprising and discouraging considering the importance of sun-and-sand tourism to the country. The present study applies the Travel Cost Method (TCM) to assess the non-market user value of three Atlantic beaches in southern Spain. The results reveal that there are statistically significant differences in visitor type by season and by beach. Calculations show that the socioeconomic benefits generated by one hectare of any of the studied beaches during the high season are one order of magnitude greater than the average annual amount of capital invested in coastal management projects and actions. It is apparent that expenditure on management strategies for the beaches of Cadiz is justified. Policy-makers should recognise that the consumer surplus is an important component of economic value because it represents a measure of social benefits rather than on-site expenditures alone. Highlights: Non-market user value of beach recreation in Spain assessed using travel cost method. The consumer surplus is used to estimate the social value of three beaches. There are significant differences in types of beachgoer between seasons and beaches. The beaches' social value greatly exceeds the capital invested into maintaining them.